Invisible population the place of the dead in East Asian megacities - Aveline-Dubach, Natacha (Lexington Books, 2012)
"Provides new information on funerary practices in East Asia's largest cities in which spatial constraints and the secularization of lifestyles are driving innovation. It reveals common trends in Japan, China and Korea, and addresses emerging challenges such as urban sustainability and growing social inequities."--Publisher's description.